(untitled) (Journal of Health Sciences, 2021)
Introduction: Carrying a school bag is a dominant activity that a child performs during daily productive activities. The aim of the research is to examine how carrying a school bag of different weights affects the distribution of force and plantar pressure during normal walking on the flat terrain of children of varying levels of physical activity.Methods: The pilot study included 124 students aged 11-12 from Banja Luka. According to the protocol, each group of respondents was treated with an intervention-customized school bag and a comparator-school bag that the child only opted for. For the research, the Physical Activity Questionnaire for Older Children, measurement of anthropometric parameters, school bag weight, and Zebris tape (Zebris Medical GmbH, Germany) were used for gait analysis.Results: Inactive children achieved the lowest and active children’s highest walking speed during normal walking without a bag, with their customized school bag. When carrying a custom school bag: The highest maximum force is projected on the left heel 330.72 N in inactive children, and the lowest 265.93 N in moderately active children, the highest maximum pressure on the left heel is registered in inactive children, 27.60 N/cm2, and the lowest 21.85 N/cm2 in moderately active children. The maximum force-time of % of standing time on the left foot in the middle part lasted the longest in inactive children, and the shortest active children carried their school bag 40.31% and a custom school bag 39.76%.Conclusion: High physical activity and individual adjustment to distribute the burden well allow the child to adequately respond to the loads carried by the weight of the school bag.